Theodora : a novel - Du Bois, Dorothea, 1728-1774; Cogan, Lucy (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This scholarly edition of Du Bois's 1770 novel, Theodora, A Novel, introduces readers to a unique voice in women's writing of the eighteenth century that has been undeservedly dismissed by literary history for far too long"--
Introduction -- Bibliography -- A Brief Chronology of Dorothea Du Bois and the Contested Inheritance of 6th Earl of Anglesey's Estate -- Note on the Text -- Theodora, a Novel, Volume 1 -- Theodora, a Novel, Volume 2 -- Appendix A: "A True Tale" from Poems on Several Occasions -- Appendix B: The Case of Ann Countess of Anglesey.
Keywords: Du Bois, Dorothea, -- 1728-1774.; LITERARY CRITICISM / Women Authors; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh